Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1042/bcj20160780
|View full text |Cite
|
Sign up to set email alerts
|

The lysosome: a crucial hub for AMPK and mTORC1 signalling

Abstract: Much attention has recently been focussed on the lysosome as a signalling hub. Following the initial discovery that localisation of the nutrient-sensitive kinase, mammalian target of rapamycin complex 1 (mTORC1), to the lysosome was essential for mTORC1 activation, the field has rapidly expanded to reveal the role of the lysosome as a platform permitting the co-ordination of several homeostatic signalling pathways. Much is now understood about how the lysosome contributes to amino acid sensing by mTORC1, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
159
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(162 citation statements)
references
References 112 publications
3
159
0
Order By: Relevance
“…Activation of AMPK and inactivation of eEF2 point to a metabolic stress response, which can be associated with autophagy [33]. Moreover, particles are reported to induce autophagy as an attempt to degrade foreign material [34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of AMPK and inactivation of eEF2 point to a metabolic stress response, which can be associated with autophagy [33]. Moreover, particles are reported to induce autophagy as an attempt to degrade foreign material [34].…”
Section: Resultsmentioning
confidence: 99%
“…AMPK initiates autophagy by direct phosphorylation of ULK1, whereas p38 MAPK induces autophagy via beclin-1 synthesis upon activation of the transcriptional function of p53 [25, 33, 36]. In contrast to ULK1 phosphorylation, beclin-1 synthesis was not upregulated in the BEAS-2B cells exposed to PM 2.5 , because p53 is inactivated by the SV40 large T-antigen in these cells.…”
Section: Discussionmentioning
confidence: 99%
“…The group that performed the current study showed previously 10 that glucose deprivation triggers the formation of a protein complex at the surface of intracellular vesicles called lysosomes, which act as intracellular wastemanagement stations 11 . The complex includes: the protein v-ATPase; a LAMTOR1-Ragulator subcomplex; the AMPK-activator LKB1; its binding partner axin; and AMPK itself.…”
Section: Energy Sensing Through a Sugar Diphosphatementioning
confidence: 99%
“…Does AMPK have a specific role associated with the lysosome? The enzyme is involved in initiating an intracellular digestion process called autophagy, by promoting formation of vesicles called autophagosomes 11 . It therefore seems reasonable that lysosomal AMPK has a role in fusing the autophagosome to the lysosome -a key step in autophagy.…”
Section: Energy Sensing Through a Sugar Diphosphatementioning
confidence: 99%
“…The energy sensor Snf1-related protein kinase 1 (SnRK1) is a heterotrimeric complex that has been suggested to be a master regulator of metabolism in plants in response to nutrient and energy deficiency (Sugden et al, 1999;Baena-González et al, 2007;Crozet et al, 2014). The animal and yeast orthologs of SnRK1, AMP-activated kinase (AMPK) and Suc nonfermenting 1 (Snf1), respectively, are energy and metabolic sensors that maintain cellular homeostasis and activate autophagy under low-energy conditions (Hardie, 2011;Carroll and Dunlop, 2017). AMPK/Snf1 can regulate autophagy by inhibiting the target of rapamycin (TOR) complex (Lee et al, 2010), a negative regulator of autophagy, therefore allowing autophagy to become active, or by direct phosphorylation of ATG1, which also leads to the activation of autophagy (Wang et al, 2001;Egan et al, 2011;Kim et al, 2011).…”
Section: Snrk1 Activates Autophagy In Response To Abiotic Stressmentioning
confidence: 99%